FIRST AID PROCEDURES FOR ACCIDENTS IN SCOUTING NATURAL EXPLORATION ACTIVITIES - Nurainun Rahmadani S; Abdillah Nasution; Salsabil Beli Ulayya (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques carried out in this research are as follows: (1) Observation (Observation, documentation and traiangulation. Research results. A first aid kit or first aid box is a place or container containing tools. first aid kit that can be used in the event of an emergency or injury to a person and to prevent a higher level of injury severity. First aid kit is equipment that should be ready at home, in the office or in a vehicle as first aid in an accident. Efforts This assistance is aimed at reducing pain, preventing the possibility and situation that will make the victim worse, providing a guarantee of safety for the victim's life and so on. First aid kits are not a treatment medium, the aim is to relieve the sufferer's wounds, prevent the victim from getting worse, and supports healing. Victims of road accidents are often not treated properly, even though with a standard first aid kit, bleeding can be stopped, even temporarily. While waiting for first aid to arrive, if conditions permit you can provide first aid using a first aid kit